Heart–kidney transplant versus heart transplant in the obese: a propensity-matched analysis. (19th December 2022) - Weingarten, Noah; Iyengar, Amit; Herbst, David Alan; Helmers, Mark; Rekhtman, David; Song, Cindy; Kim, Samuel T; Atluri, Pavan
Abstract: OBJECTIVES: The decision to perform simultaneous heart–kidney transplant (HKT) rather than isolated heart transplant (IHT) for patients with advanced kidney disease is challenging. Limited data exist to guide this decision in obese patients. We sought to compare mortality after HKT and IHT in obese patients with non-dialysis-dependent kidney disease. METHODS: The United Network for Organ Sharing was queried for data on adult heart transplant recipients from 2000 to 2022. Inclusion criteria were obesity, estimated glomerular filtration rate <45 ml/min/1.73 m 2 and no pretransplant dialysis. HKT and IHT recipients were propensity matched. Morbidity was compared using chi-squared, Fisher's exact and McNemar's tests. Survival was assessed with Kaplan–Meier estimation. Risk factors for mortality were examined with Cox regression. RESULTS: A total of 289 HKT and 1920 IHT recipients met inclusion criteria. Heart–kidney recipients had higher baseline creatinine and rates of intensive care unit disposition than IHT recipients (both standardized mean differences >0.10). Propensity matching resulted in 239 pairs of HKT and IHT recipients with minimal differences in baseline characteristics. Heart–kidney recipients had higher 5- and 10-year survival than IHT recipients on unmatched (77% vs 69%, P = 0.011 and 58% vs 48%, P = 0.008) and propensity matched analyses (77% vs 68%, P = 0.026 and 57% vs 39%, P = 0.007). Heart–kidney transplantation was protective against 10-year mortality on multivariable regression (hazard ratio 0.585, P = 0.002). CONCLUSIONS: In obese patients with non-dialysis-dependent kidney disease, HKT may decrease long-term mortality relative to IHT and should be strongly considered as a preferred treatment. Abstract : Patients with concomitant end-stage heart disease and chronic kidney disease (CKD) may benefit from either heart–kidney transplant (HKT) or isolated heart transplant (IHT).